From Ideological Reflection to Pedagogical Reality - D. Expósito, Cristián (2018)
It is not possible to speak of education without values, nor is it possible to speak of culture without ideology. In the same way that values shape and give meaning toeducation, ideologies shape cultures. Values are responsible for the actions of people, institutions and societies, however, these are ordered based on ideologies. It is ideology that unites the environment of the person with his own identity,it is the bridge between the social macro and the social micro; an immeasurable concept composed of personal values, beliefs and certain ways of thinking that provide an explanation of the world in which we live. The educational systems of countries are regulated by a series of axiological principles that respond to a preponderant social model. The danger of these ideological models underlies the reductionism that can plunge a community into something less than obscurantism. In this work the relationship between ideologies, values, culture and education is explained starting from the conceptualizations of the three most influential ideologies in Latin American education: Christianity, Marxism and Anarchism.